Petani Rasional: Gambaran Petani Benculuk Pasca Masuknya Mesin Combine Harvester - Sholihah, Indri Maratus; Mulyono, Joko; Paramitha, Nurina Adi (Jurnal Sosiologi Pertanian dan Agribisnis, 2024)
Abstract: The combine harvester machine entered and was adopted by farmers in Benculuk Village in October 2020. The combine harvester machine entered Benculuk Village due to several driving factors, namely the lack of a number of harvest workers, the mobility of farm workers to other jobs, the use of a combine machine that is more practical and efficient, the yield cleaner and more optimal, and farmers keep abreast of existing trends. Because after the introduction of the combine harvester machine it has been proven to be able to provide benefits for farmers including being able to minimize the level of crop loss, increase crop production, improve the quality of rice yields, and efficiency in the use of costs, time and energy expended. The purpose of this study was to examine the description of the rationality of farmers in Benculuk Village after the combine harvester machine was introduced. This study uses the theory of rational farmers from Samuel L. Popkin (1986). The method used is qualitative with a phenomenological approach. Where the research location is in Benculuk Village, Cluring District, Banyuwangi Regency. The findings from this study after the introduction of the combine harvester machine to farmers in Benculuk Village changed the life order of the farmers who used it. The changes that are felt have an impact on changes in civilization, namely changes in the technological machines used by farmers when they go to paddy fields. Ecological changes that make paddy soil more muddy and watery. Economic changes, namely farmers are more profitable, as well as changes in the social life of landowners and farm workers. After the introduction of the combine harvester machine in Benculuk Village, it shows that the farmers there have become rational farmers who lead to capitalism.